CLIMATE CHANGE ECONOMICS: MITIGATION POLICIES AND ADAPTATION STRATEGIES - Judijanto, Loso (Economics Studies and Banking Journal (DEMAND), 2024)
Climate change is a significant global challenge, affecting economic stability and food security in various countries. This research aims to evaluate the effectiveness of mitigation and adaptation policies in increasing economic resilience, especially in countries that are vulnerable to the impacts of climate change. This study focuses on analyzing mitigation and adaptation policies implemented in various countries, as well as their impact on economic resilience and social sustainability. This research uses a Systematic Literature Review (SLR) approach with the PRISMA protocol to identify, assess, and synthesize relevant literature. Data were collected from peer-reviewed articles in the Scopus, Web of Science, and ScienceDirect databases, with meta-synthesis and comparative analysis to identify patterns and policy effectiveness. The findings show that a combination of mitigation policies, such as carbon taxes and emissions trading, and adaptation strategies, such as green infrastructure and economic diversification, significantly improves economic resilience. Countries with strong political support and investment in green technology show better results. This research provides important insights for policymakers to design more effective strategies in dealing with climate change, by emphasizing the need to integrate mitigation and adaptation policies to achieve sustainable economic resilience.